Cancer-Selective Induction of Apoptosis by Leczyme - Tatsuta, Takeo; Sugawara, Shigeki; Takahashi, Kohta; Ogawa, Yukiko; Hosono, Masahiro; Nitta, Kazuo (Frontiers in Oncology, 2014)
Sialic acid-binding lectin (SBL) is a multi-functional protein that is isolated from oocytes of Rana catesbeiana. It has both lectin and ribonuclease (enzyme) properties, and therefore is called leczyme. We examined the anti-tumor effects of SBL and discovered that SBL has potential as a new type of anti-cancer drug. SBL causes a cancer-selective induction of apoptosis by multiple signaling pathways whereby RNA is its target. It is suggested that the mitochondrial pathway and endoplasmic reticulum stress-mediated pathway participate in SBL-induced signaling. The synergistic anti-tumor effects with other molecules, such as tumor necrosis factor-related apoptosis ligand and interferon γ, have been reported. In this study, we summarize the effects of SBL and focus on its cancer-selective apoptotic properties. In addition, we present a possible explanation for its cancer specificity.